2019
DOI: 10.3389/fimmu.2019.00070
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of IL-1β From Monocytes in Gout Is Redox Independent

Abstract: The pro-inflammatory cytokine interleukin-1β (IL-1β) plays important roles in immunity but is also implicated in autoimmune disease. The most well-established mechanism of IL-1β secretion is via activation of the NOD-like receptor family pyrin domain containing-3 (NLRP3) inflammasome which requires an initial priming signal followed by an activating signal. However, the precise mechanism by which the inflammasome is activated remains unclear. The role of reactive oxygen species (ROS) in this process is contrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Pharmacologic inhibition of the NLRP3 inflammasome is a promising strategy to treat a variety of inflammatory diseases (Mangan MS et al, 2018). However, such therapeutic approach may not be useful in gout as the expression levels of NLRP3 inflammasome components in circulating monocytes from gout patients were shown not to be different from those of normal subjects (Alberts BM et al, 2019). Rather, an anti-inflammatory effect in urate crystal stimulated monocytes can be achieved independent of the NLRP3 inflammasome as demonstrated with FTY720-P where it reduced IL-1 secretion by monocytes without altering caspase-1 activity or NLRP3 protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic inhibition of the NLRP3 inflammasome is a promising strategy to treat a variety of inflammatory diseases (Mangan MS et al, 2018). However, such therapeutic approach may not be useful in gout as the expression levels of NLRP3 inflammasome components in circulating monocytes from gout patients were shown not to be different from those of normal subjects (Alberts BM et al, 2019). Rather, an anti-inflammatory effect in urate crystal stimulated monocytes can be achieved independent of the NLRP3 inflammasome as demonstrated with FTY720-P where it reduced IL-1 secretion by monocytes without altering caspase-1 activity or NLRP3 protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular injection of MSU-induced inflammatory arthritis could result from UA injection [ 57 ]. Although both SUA and MSU crystals can stimulate immune responses, different pathways have been demonstrated between them from epigenetic regulation, inflammasome activation to transcriptional control [ 58 ], and the immune reactions created by them are different inactivation and priming [ 59 ] through various proinflammatory pathways [ 60 ] involve in circulating monocytes and/or resident macrophages. UA released from dying cells during inflammation reactions could prime new monocytes and precipitate onto MSU crystals leading to more inflammation and tissue damage.…”
Section: Distinct Reaction and Priming Pathways Of Inflammation Bymentioning
confidence: 99%
“…Previous studies demonstrated that no difference is observed in the mRNA level of IL-1β after the MSU crystal-based stimulation of macrophage, suggesting a lack of the priming effect of MSU in in ammasome activation [7]. In line with these ndings, MSU itself failed to induce IL-1β secretion [8]. Therefore, it is unclear what priming stimuli trigger gout attacks in patients with hyperuricemia.…”
Section: Introductionmentioning
confidence: 83%